STUDENTS’ PSYCHOLOGICAL FACTORS IN SLA: A DILLEMA FOR TEACHERS OF ENGLISH - Budianto, Langgeng (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2010)
This paper aims at describing psychological factors in language acquisition and learning for human being who learn second language acquisition. Stephens found that external factors such as the characteristic of teacher, class and school condition had consistently no relation with the success of learning foreign language. On the other hand, student’s psychological conditions, as one of the internal factors, are potential to influence the foreign or second language acquisition. Psychological factor is a factor that is mentally or spiritually concerned with the aspects in students’ acquisition. At least, four of many factors, such as anxiety, attitude, aptitude, and motivation influence the students’ process of language acquisition. However, to cope the psychological problems of learning second language, Kando, D. suggests the five strategies for coping with language anxiety, among of them are preparation strategy, relaxation, positive thinking, peer, and labeled resignation. Therefore, in maximizing the result of second language acquisition, the five strategies illustrated by Kando are important as an alternative solution.